Multimodal Existential Negation in Ecuadorian Highland Kichwa - Simeon Floyd (Languages, 2025)
Conventionalized or symbolic “emblematic” visual expressions are the types of “gesture” that most closely resemble lexical and grammatical elements seen in spoken languages or in sign languages in the visual modality. The relationship between conventionalization in the visual modality and in morphosyntax is a topic that remains only partially explored, with more research focused on iconic and indexical aspects of visual expression than on symbolic aspects. However, the culture-specific nature of symbolic gestures makes them an important phenomenon for the study of cultural variation at the intersection of modality and linguistic diversity. This study examines the relationship of a specific area of morphosyntax, negation and syntactic polarity, to an element of the visual modality, a practice of visual existential negation used by speakers of Imbabura Kichwa, a variety of Ecuadorian Highland Kichwa, a Quechuan language spoken in the Ecuadorian Andes. A data set of natural speech recordings will illustrate this open-handed rotating gesture that expresses negative existence: “there is none”. This gesture will be analyzed in terms of its form, meaning, and combination with spoken elements in discourse context, finding that in this variety of Kichwa, this practice is associated with a specific verb root meaning “to lack” or “to not exist”. This discussion will be framed in the wider context of the areal distribution of similar types of visual existential negation in other languages of Ecuador, reflecting the diversity of multimodal conventionalization across speech communities.